Nikah Gantung in Legal and Social Discourse: The Contestation of Legality between State, Religion, and Custom - Zukhrufil Shadri; Rintia Rintia; Md Shahidur Rahman Shakil (CV. Austronesia Akademika, 2025)
ABSTRACT Nikah gantung is a marriage practice that is religiously valid, yet the couple does not live together or fulfill domestic obligations such as financial support. This phenomenon is commonly found in several traditional communities in Indonesia, primarily as an effort to preserve family honor, avoid premarital sex, or due to economic reasons. However, behind this practice lies a serious discrepancy between religious norms, customary law, and state legal regulations—particularly in terms of marriage registration, legal protection, and minimum marriage age. This study aims to critically analyze the tension among religious, customary, and state institutions in defining the legality of nikah gantung. It also explores how the power relations among these three institutions shape the meaning of what constitutes a